2010
DOI: 10.1186/ar3173
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of adhesion molecule-mediated chondrocyte-matrix interactions by 4-hydroxynonenal binding: implication in osteoarthritis pathogenesis

Abstract: IntroductionObjectives were to investigate whether interactions between human osteoarthritic chondrocytes and 4-hydroxynonenal (HNE)-modified type II collagen (Col II) affect cell phenotype and functions and to determine the protective role of carnosine (CAR) treatment in preventing these effects.MethodsHuman Col II was treated with HNE at different molar ratios (MR) (1:20 to 1:200; Col II:HNE). Articular chondrocytes were seeded in HNE/Col II adduct-coated plates and incubated for 48 hours. Cell morphology wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…41 El-Bikai et al supported this concept by showing that ICAM-1, integrin a 1 b 1 , MMP13, extracellular signal-regulated kinases 1 and 2, and COX-2 were strongly upregulated in chondrocytes cultured over 4-hydroxynonenal anchored collagen 2 fibrils. 42 These findings indicate that the intimate interaction between receptors of chondrocytes with inflammatory mediators anchored to the underlying matrix or modulated matrix composition initiates cascades of signaling pathways triggering early features of OA pathogenesis.…”
Section: Tissue-engineered Model Of Osteoarthritismentioning
confidence: 94%
“…41 El-Bikai et al supported this concept by showing that ICAM-1, integrin a 1 b 1 , MMP13, extracellular signal-regulated kinases 1 and 2, and COX-2 were strongly upregulated in chondrocytes cultured over 4-hydroxynonenal anchored collagen 2 fibrils. 42 These findings indicate that the intimate interaction between receptors of chondrocytes with inflammatory mediators anchored to the underlying matrix or modulated matrix composition initiates cascades of signaling pathways triggering early features of OA pathogenesis.…”
Section: Tissue-engineered Model Of Osteoarthritismentioning
confidence: 94%
“…In the presence of α1 or β1 blocking antibodies the induction of MMP‐13 expression was inhibited (Ronziere et al, ). Furthermore, a recent report has suggested that collagen II fibrils modified by the lipid peroxidation end‐product 4‐hydroxynonenal, which is upregulated in synovial fluid of OA patients, induce cell death and catabolic and inflammatory responses of human AC chondrocytes, presumably through perturbation of α1β1 signaling (El‐Bikai et al, ).…”
Section: Synovial Joint and Acmentioning
confidence: 99%
“…As an example, HNE binding to type II collagen and the consequent ALE product results in signal transduction, inducing multiple abnormalities of chondrocytes phenotype and function, suggesting its contribution in osteoarthritis development (El-Bikai et al 2010). AGEs can also induce vascular smooth muscle proliferation via a prolonged agonist-induced Ca 2?…”
Section: Mechanisms Of Ages and Ales Formation And Their Biological Imentioning
confidence: 99%